Response surface methodology-based optimized ultrasonic-assisted extraction and characterization of selected high-value components from Gemlik olive fruit - Ullah, Sami; Anwar, Farooq; Fayyaz ur Rehman, Muhammad; Qadir, Rahman; Safwan Akram, Muhammad (Wiley, 2023)
This article presents an optimized ultrasound-assisted ethanolic extraction (UAEE) and characterization of selected high-value components from Gemlik olive fruit (GOF) harvested from Potohar region of Pakistan. Response surface methodology (RSM), involving central composite design (CCD), was applied to optimize the extraction variables i. e., temperature (25–65 °C), extraction time (15–45 min) and aqueous ethanol concentration (60–90 ) for optimal recovery of bioactives extract, total phenolic contents (TPC) and DPPH free radical scavengers. Under the optimized set of conditions such as 43 °C temperature, 32 min extraction time and 80 aqueous ethanol, the best extract yield (218.82 mg/g), TPC (19.87 mg GAE/g) and DPPH scavenging activity (63.04 ) were recorded. A quadratic polynomial model was found to be reasonably fitted to the observed results for extract yield (p<0.0001 and R2=0.9941), TPC (p<0.0001 and R2=0.9891), and DPPH radical scavenging activity (p<0.0001 and R2=0.9692). Potent phenolic compounds were identified by GC/MS in GOF extract and considerable amount of essential fatty acids were also detected. The current findings support the use of UAEE as an effective green route for optimized recovery of high-value components from GOF and hence its applications can be extended to functional food and nutra-pharmaceutical developments.